2007
DOI: 10.1111/j.1467-9256.2007.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Another Side of the Story: A Qualitative Case Study of Voting Behaviour in the European Parliament

Abstract: This study re‐examines the conclusions drawn from existing research on legislative behaviour in the European Parliament (EP). Using written questionnaires and qualitative interviews with all 14 current Danish Members of the European Parliament (MEPs) and three former MEPs, existing academic findings on voting behaviour in the EP are compared and contrasted with ground‐level experience from the MEPs' point of view. This study lends support to many of the conclusions drawn from previous quantitative research. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Some recent publications have similarly shed new light on voting determinants in the EP by using qualitative, interview-based methods. For example, a study conducted on a sample of Danish MEPs showed national affiliation to play a much stronger role than previously acknowledged in areas such as employment, environment and agricultural policy, where MEPs seem to follow national interests rather than ideological positions (Rasmussen 2008). The same goes for another recent survey of MEPs' policy preferences, conducted in 2010, which found that the Member State of origin is a more powerful predictor of general MEPs' attitudes than the EP party group affiliation (Farrell et al 2012).…”
Section: Related Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…Some recent publications have similarly shed new light on voting determinants in the EP by using qualitative, interview-based methods. For example, a study conducted on a sample of Danish MEPs showed national affiliation to play a much stronger role than previously acknowledged in areas such as employment, environment and agricultural policy, where MEPs seem to follow national interests rather than ideological positions (Rasmussen 2008). The same goes for another recent survey of MEPs' policy preferences, conducted in 2010, which found that the Member State of origin is a more powerful predictor of general MEPs' attitudes than the EP party group affiliation (Farrell et al 2012).…”
Section: Related Literaturementioning
confidence: 93%
“…Another related critique to RCV research has been moved by scholars underlining that pooling all data hides interesting variance across issue areas and across voting procedures (Gische 2007;Rasmussen 2008;Cicchi 2013). One study on EU trade policy, while confirming that MEPs vote prevalently in line with EP party groups, found that on highly sensitive issues some national delegations vote along their national interests and against the dominant position of their EP party groups (Kang 2013).…”
Section: Related Literaturementioning
confidence: 99%
“…A study on Turkey's accession to the EU may serve as an example: it consists in spatial analyses that determine the extent to which the opinions of individual MEPs differ (Braghiroli 2012). Additional studies focus not primarily on RCV, but rather seek out the determinants of MEP behaviour by examining the votes of individual MEPs under RCV (Rasmussen 2008, Yuvaci 2013.…”
Section: Study Of Mep Behaviourmentioning
confidence: 99%
“…Research on political groups has often been quantitative and focused on macro‐level power relations, such as voting patterns, group cohesion and relations to national parties and politics to explain the significance and role of political groups in EP policy‐making (Hix, 2008; McElroy and Benoit, 2010; Raunio and Wagner, 2017). However, an emerging body of literature using qualitative and mixed methods has begun to detail the ways that power works at the microlevel of politics, exploring the role of informality, meanings and actors in decision‐making processes (Berthet and Kantola, 2020; Brack, 2018; Häge and Ringe, 2020; Rasmussen, 2008; Ripoll Servent and Panning, 2019). The starting point for this article is that qualitative studies can capture existing power relations not just on a macro level but within and between political groups; including democratic practices and their erosion and conditions for equal political representation and participation at the heart of democratic functioning of these institutions.…”
Section: Introductionmentioning
confidence: 99%